DEKOMPOSISI DAN MINERALISASI KADAR N BOKASHI PUPUK KANDANG KOTORAN AYAM - Widowati Widowati; I Made Indra Agastya (Universitas Tribhuwana Tunggadewi, 2015)
Aims of the study is to evaluate the decomposition and mineralization Nitrogen of bokashi chicken manure made by litter and battery systems. Litter system ussually developed the floor of cage cover by the form of sawdust and rice husk but baterry with cage type of tenuous and perforated floor. Soil incubation of bokashi experiment was conducted in the laboratory and in field the Village Tunggulwulung, Malang. Incubation activities with five sample in the laboratory laid under conditions with and without leached. Observation was made in amount of nitrogen for 2, 4, 6, and 8 weeks. Bokashi manure decomposition of chicken manure was observed in litter bag using method recommended by the Tropical Soil Biology and Fertility. Bags of litter were observed at 1, 2, 4, 8, and 14 weeks. The amount of mineral N in KCl extracts - soil determined using Kjeldahl distillation method. Results of research showed that on leached condition leached mineralization at 2, 4, 8, and 14 weeks bokashi batery lower compared with litter by 0.8, 8, 0.2, 0.6 t N/ha and 0.3, 10, 13, 0.8 t N/ha respectively